Sometimes conventional removable partial denture is the only remedy! - Nihel, Charfi; Imed, Ouni; Lamia, Mansour; Mounir, Trabelsi (Journal of Nepalese Prosthodontic Society, 2021)
Management of partially edentulous patients can still be a prosthodontic challenge especially for extensive maxillary Kennedy Class I. Replacing the missing teeth using conventional fixed and removable partial dentures (FPD/RPDs) associated with extracoronal attachments remains sometimes the only remedy for partial edentulism. The use of osseointegrated dental implants turn the possibilities of prosthetic reconstruction endless, but what about patients with absolute contraindication of surgery. It is therefore the objective of this article to describe the treatment sequence and technique for the use of attachments in therapy combining FPD/RPD.